2014
DOI: 10.1080/02134748.2013.878571
|View full text |Cite
|
Sign up to set email alerts
|

Intention of activism and radicalism among Muslim and Christian youth in a marginal neighbourhood in a Spanish city / Intención de activismo y radicalismo de jóvenes musulmanes y cristianos residentes en un barrio marginal de una ciudad española

Abstract: The aim of this research is to assess the intended level of religious and political activism and radicalism in a sample of Muslim and Christian youth living in a marginalised neighbourhood in a southern city in Spain. Interrelations between activism and radicalism and other psychosocial factors potentially contributing to religious and political mobilisation processes are analysed, such as group identification, self-esteem, violent disinhibition, religious extremism and perceived oppression. Important differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 25 publications
1
25
0
4
Order By: Relevance
“…Estos hallazgos pueden estar justificados por el estudio de Moyano y Trujillo (2014), quienes destacan cómo la comunidad musulmana muestra una mayor adhesión a su religión con respecto a la cristiana -que muestra una mayor división en la identidad religiosa. Asimismo, diversos estudios muestran cómo una mayor espiritualidad puede relacionarse con un mayor bienestar psicológico y social en ciertas religiones (Mensah, 2014;Moyano y Trujillo, 2014;Vinaccia et al, 2012).…”
Section: Discusión Y Conclusionesunclassified
“…Estos hallazgos pueden estar justificados por el estudio de Moyano y Trujillo (2014), quienes destacan cómo la comunidad musulmana muestra una mayor adhesión a su religión con respecto a la cristiana -que muestra una mayor división en la identidad religiosa. Asimismo, diversos estudios muestran cómo una mayor espiritualidad puede relacionarse con un mayor bienestar psicológico y social en ciertas religiones (Mensah, 2014;Moyano y Trujillo, 2014;Vinaccia et al, 2012).…”
Section: Discusión Y Conclusionesunclassified
“…Additionally, several studies remain at a theoretical level or use a population-based sample that provides only indirect tendencies (Schmid, 2013). Some authors chose to focus on the degree of sympathy towards radicalism and extremist beliefs Moyano and Trujillo, 2014). Empirical data regarding females and non-Muslim communities are lacking, as well as longitudinal studies investigating programs for de-radicalization.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, in a field investigation developed in a vulnerable urban environment, Moyano and Trujillo (2014) found a significant relationship between perceived oppression, radical intentions, and violent disinhibition in a Muslim sample, whereas the same relations were not significant in a sample of Christians. They concluded that these results are due to a greater cohesion with religion on the part of the Muslim sample and the context’s demographic characteristics, which include the perception of an out-group threat residing in a marginal neighborhood.…”
Section: The Role Of Identity and Culturementioning
confidence: 92%
“…Violent disinhibition refers to the desire to end one’s own life or that of others, a high negative emotionality (hostility, dislike, aversion, hatred, anger, and tension), and the observational learning of violent behavior (Trujillo, 2009; Moyano and Trujillo, 2013, 2014; Trujillo and Moyano, 2018). Likewise, for a subject to act decisively to commit terrorist acts, usually there is a prior event or circumstance that precipitates the radicalization process (e.g., a grievance).…”
Section: From Oppression To Violencementioning
confidence: 99%
See 1 more Smart Citation